The CBFM-Enhanced Jacobi Method for Efficient Finite Antenna Array Analysis - Ludick, D.; Botha, M.; Maaskant, R.; Davidson, David (Institute of Electrical and Electronics Engineers, 2017)
© 2017 IEEE. An enhancement to the iterative Jacobi technique with the characteristic basis function method is presented. The resulting method is intended for efficient method of moments (MoM)-based analysis of large, disjoint finite antenna arrays. The enhancement improves the convergence rate of the Jacobi method by better accounting for mutual coupling between array elements. This involves solving a small, global problem at each iterative step, using macrobasis functions that are iteratively generated. Results are presented, and it is found that the proposed method can recover fast convergence in cases where the Jacobi method diverges or converges slowly. The proposed method also converges significantly faster than a conventional, preconditioned, iterative solution of the MoM matrix equation.